2008
DOI: 10.1513/pats.200802-020sk
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life and Patient-reported Outcomes in Pulmonary Arterial Hypertension

Abstract: Advances in our understanding of the basic pathophysiology of pulmonary arterial hypertension (PAH) has led to an expanding number of therapeutic options. The ultimate goals of therapy are to lengthen survival while improving symptoms and quality of life. A wealth of research in other conditions has established health-related quality of life (HRQoL) to be an important clinical endpoint. Until recently, however, little was known about HRQoL in PAH, and how best to measure it. Over the past few years, several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 45 publications
3
79
2
4
Order By: Relevance
“…9,10 Several studies evaluating health status and HRQL in PAH combine the etiologies and report as a single cohort 11 ; several pharmacological studies have measured health status and/or HRQL as end points to determine treatment efficacy. [11][12][13][14][15][16] A comparison of HRQL between patients with various PAH etiologies (n = 155) showed that patients with IPAH had better HRQL than those with systemic sclerosis, although HRQL was diminished in all patients with PAH.…”
Section: Health Status and Hrqlmentioning
confidence: 99%
“…9,10 Several studies evaluating health status and HRQL in PAH combine the etiologies and report as a single cohort 11 ; several pharmacological studies have measured health status and/or HRQL as end points to determine treatment efficacy. [11][12][13][14][15][16] A comparison of HRQL between patients with various PAH etiologies (n = 155) showed that patients with IPAH had better HRQL than those with systemic sclerosis, although HRQL was diminished in all patients with PAH.…”
Section: Health Status and Hrqlmentioning
confidence: 99%
“…When previously studied, multiple studies have noted QOL for patients with PAH is poor or sub-optimal, [13][14][15][16][17][18] However, to our knowledge, the incorporation of PC into a management plan for PAH has not been evaluated. To better understand the need for such an intervention, this study evaluated symptom burden, QOL, and attitudes regarding PC in a large, international sample of PAH patients and was aimed at identifying barriers to effective PC as well as characterizing opportunities to improve QOL in PAH patients.…”
mentioning
confidence: 99%
“…12 Changes in physiological measures may not always translate into benefits that can be perceived by the patient. 13 Some studies of patients with PH have provided controversial results and have questioned whether improvement in QOL is associated with improvements in laboratory data, hemodynamics, exercise capacity, and survival. 14 Therefore, health-related QOL is often measured as an additional endpoint.…”
Section: Surgical Treatmentmentioning
confidence: 99%